ANALISIS PENGELOLAAN VALUTA ASING TERHADAP PROFITABILITAS PT GARUDA INDONESIA (PERSERO) TBK - Haq, Akhsanul; Muniroh, Andir (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2015)
In 2013 the company also invested large amounts in the form of additional fleets to support operational improvements financed with foreign currency debt. For the use of these debts, the company must pay the credit debt periodically. The decline in the rupiah against the US dollar led to a growing number of rupiah funds should be spent. This study aims to determine how the management of foreign exchange through the method of hedging against the profitability of the main indicators of profit or loss on foreign exchange of PT Garuda Indonesia (Persero) Tbk using secondary data such as financial statements and annual report of PT Garuda Indonesia (Persero) Tbk and spreads forward and call spread option. The analytical method that used is the method of simulation on alternative methods of hedging foreign exchange rates. Results of the study revealed that the cross currency swap contracts held by the company in 2014 have shown positive results where PT Garuda Indonesia (Persero) Tbk can make a profit of USD 29 770. Because financially, hedging is only intended to protect the interest payments on loans and credit bond investment, the company still has the potential to bear the profit or loss on the change in exchange rates other operations against the US Dollar.Â Keywords: Management of foreign exchange, cross bilateral swap transaction, forward contracts, call option, the cost of hedging, profitability, and profit and loss on foreign exchange.Â Â